Factors influencing cloud computing adoption in the public sector: an empirical analysis - Hasimi Sallehudin; Razli Che Razak; Mohammad Ismail (http://fkp.umk.edu.my/journal/download/3-v3.pdf, 2015)
- Cloud computing is one of the latest Information Technology innovation phenomena that has risen from the idea of sharing, consolidating, and standardizing of resources in a centralized infrastructure and facility. This concept offers many advantages such as cost reduction in both hardware and software investment for organizations. Despite these advantages, cloud computing adoption among organizations is relatively slow with a low adoption rate. As such, this study attempts to bridge the gap by offering insight into possible factors that could influence such adoption decisions. By integrating the Diffusion of Innovation Theory (DOI) and IT personnel characteristics, a conceptual model is developed and tested as a preliminary study to determine the influencing factors of cloud computing adoption by the Malaysian public sector to enhance its service delivery. The results revealed that relative advantage, compatibility, and IT personnel knowledge are the innovation attributes and the human factor for cloud computing adoption in the Malaysian public sector. This study contributes to the knowledge domain of cloud computing adoption literature on theories of IT adoption particularly in the public sector.